Guru PPKn Dalam Membangun Karakter Kedisiplinan Siswa Di SMA Negeri 1 Pollung - Lammarito Lumban Gaol; Liber Siagian; Jamaludin; Sri Yunita; Oksari A. Sihaloho (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
ABSTRACT This study examines Civic Education teachers’ efforts to foster discipline in students at Pollung State High School 1. The development of student discipline has not been fully effective; students tend to merely comply with rules rather than internalize them. This study employs a descriptive qualitative approach grounded in Thomas Lickona’s theory of character value internalization, which comprises moral knowing, moral feeling, and moral action. The research location is at Pollung 1 Public High School, located at Jalan Mayor (Ret.) C. Dj Marbun, Hutapaung Village, Pollung Subdistrict, Humbang Hasundutan Regency. The research informants consist of 3 Civic Education teachers and 7 students selected using purposive sampling. The data used consisted of primary and secondary data. Primary data was obtained through observation, interviews, and documentation, while secondary data was sourced from scientific literature and relevant official documents. The data analysis technique used the Miles and Huberman model, which includes data reduction, data presentation, and data verification. The results of the study indicate that Civic Education teachers have fulfilled their roles as mentors, role models, facilitators, and motivators in building students’ character. However, the process of internalizing values has not yet been optimally implemented in fostering sustainable student discipline, as evidenced by weak internalization of character values in the aspects of moral feeling and moral action. In addition, students’ low self-awareness, the influence of social media and peer groups, and a lack of parental support remain the main challenges faced by Civic Education teachers in fostering a disciplined character among students at Pollung State High School 1. Keywords: Civic Education Teachers, Disciplined Character, Internalization Of Values ABSTRAK Penelitian ini mengkaji guru PPKn dalam membangun karakter kedisiplinan siswa di SMA Negeri 1 Pollung. Pembentukan disiplin siswa belum sepenuhnya efektif dan cenderung hanya patuh terhadap aturan namun belum terealisasikan dalam diri siswa. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan landasan teori internalisasi nilai karakter menurut Thomas Lickona yaitu moral knowing, moral feeling dan moral action. Lokasi penelitian berada di SMA Negeri 1 Pollung, yang beralamat di Jalan Mayor (Purn) C. Dj Marbun, Desa Hutapaung, Kecamatan Pollung Kabupaten Humbang Hasundutan. Informan penelitian ini terdiri dari 3 orang guru PPKn dan 7 orang siswa yang dipilih dengan teknik purposive sampling. Data yang digunakan terdiri dari data primer dan sekunder. Data primer diperoleh melalui observasi, wawancara serta dokumentasi, sedangkan data sekunder bersumber dari literatur ilmiah serta dokumen resmi terkait. Teknik analisis data menggunakan model Miles dan Huberman yang meliputi reduksi data, penyajian data dan verifikasi data. Hasil penelitian menunjukkan bahwa guru PPKn telah menjalankan perannya sebagai pembimbing, teladan, fasilitator, dan motivator dalam membangun karakter siswa. Namun, proses internalisasi nilai belum berjalan secara optimal dalam membentuk karakter disiplin siswa yang berkelanjutan, yang ditandai dengan lemahnya internalisasi nilai karakter pada aspek moral feeling dan moral action. Selain itu, rendahnya kesadaran diri siswa, adanya pengaruh media sosial dan pergaulan teman sebaya, serta kurangnya dukungan orang tua masih menjadi kendala utama yang dihadapi guru PPKn dalam membangun karakter kedisiplinan siswa di SMA Negeri 1 Pollung. Kata Kunci: Guru PPKn, Karakter Kedisiplinan, Internalisasi Nilai